Educação especial em contexto de pandemia: análise do atendimento educacional especializado - Cunha, Monica Mendes da (2022)
This thesis is part of the line research “Policies, institutional practices and social exclusion/inclusion” in Education master’s degree – Social Education concentration area – in the post-graduate program in Education of Federal University of Mato Grosso do Sul – Pantanal Campus. It focuses on studies of Special Education and School Inclusion, schooling and guaranteeing the rights of the special education students. The year 2020 began with the closing of Brazilian schools, following international recommendations, aiming control of the pandemic spread of COVID-19, forcing schools to adapt abruptly. Given this atypical educational context, this research aims to understand how the Specialized Education Attendance has occured during the pandemic, seeking analyze how social isolation may have influenced these services. In a qualitative approach, primarily develops the bibliographic review with a survey of theses, dissertations, journals articles and works published in the education area events, contributing to the refinement of the study object. Subsequently, were undertaken interviews with working teachers of Multifunctional Resource Rooms of Corumbá/MS and Mesquita/RJ, through Google Meet. The choice of the teachers and the loci was made trhough the project “Information and Communication Technology and inovation in schooling processes in inclusive education: different contexts in Brazil and Spain” which the research is integrated. The study showed differents ways of action of Specialized Education Attendance teachers with was expected in inclusion policies perspectivies, which made it difficult/difficult the best progress and development of the students who need treatment. We conclude that the teachers produced as much as possible and prepared themselves in the same proportion that they were assisted to try to continue these services. The lack of coordination from public institutions made it impossible to continue or made it with unquality to offer this treatment in the middle of the pandemic. The realization of this search seeks to contribute to the expasion of the attendance that occured in two Brazil regions (Midwest and Southeast) and, also, put in discussion a education that is inclusive and for everybody, with the intetion of collaborating with the broader debate and to promote brazilian public policies focused to special education. KEYWORDS: Inclusion Policies. Specialized Education Attendance. Covid-19. School Inclusion. Multifunctional Resource Rooms.